Inculcation Nation Character Values Through Islamic Religious Education Subject In Public Senior High School - Yustiani Yustiani (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
Cases of cheating, promiscuity, making sordid video student in the classroom are the phenomena of decline in character education at the school. In this sense, character education is essential to emphasized. This research uses qualitative approach, by applying design research CIPP model (Context, Input, Process, and Product). In context of building the nation character values at the school will success on condition that it is accompanied with system and climate supported by each school. One of supporting system and climate is the headmaster's policies on the regulation that support the implementation of character education, and this policy should be supported by infrastructure of the school. The input aspect that determines inculcation of nation character values in these both schools is the quality of the school resources including headmaster, teachers, educational staffs, students, and education infrastructures. From the aspects of process, inculcation nation character values on these schools is implemented through the integration of the Islamic religious education subject and culture of the school. Syllabus and RPP on subjects of Islamic religious education in State Senior High School 1 Kudus and State Senior High School 1 Jepara have already been insightful with the education of nation character. The aspects of product from internalization of cultural values and nation character are embodied in attitudes and behaviors of the students at school and society.